Assessment of the Impact of Zebra Mussels on the Ecosystem of the Tigris River - Meshjel, Maysoon H. (Iraqi Journal of Science, 2022)
10 sites were selected for investigating zebra mussels in the Tigris River for the study that was conducted for the period from January to December 2020. The results of this investigation showed that zebra mussels were recorded in the Tigris at Taji on sites 7, 8, 9 and 10, while it was not found in the Tigris at Kut on sites 1, 2, 3, 4, 5 and 6. This is the first time that this species was ever recorded in the Tigris. It was found that the sites where zebra mussels appeared had a clear impact on the decrease in the total organic carbon %age and turbidity (NTU). High dissolved oxygen values were observed in the sites where zebra mussels were recorded, and the appearance of zebra mussels in these sites caused a clear decrease in the appearance and total density of benthic invertebrates, in addition to a clear increase in the total density of  epiphytic algae. Zebra mussels caused the disappearance of the local species of the phylum Mollusca and crustaceans in the sites where it appeared.